1995
DOI: 10.1093/jnci/87.22.1686
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Black/White Differences in Colon Cancer Survival

Abstract: Because the racial disparity was confined to earlier stages, future studies should investigate whether blacks have more advanced disease at diagnosis and whether less aggressive treatment is provided because of understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
113
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(125 citation statements)
references
References 0 publications
9
113
2
Order By: Relevance
“…Pathologist inter-and intraobserver variation in the classification of MPA type could not be controlled for, but this would be expected to weaken rather than exaggerate the observed association with SE status. As previously reported (Mayberry et al, 1995), there is a higher risk of MPA tumour subtype in younger patients. There was a previously unreported, excess risk of MPA subtype in patients with proximal subsites tumours and in women.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Pathologist inter-and intraobserver variation in the classification of MPA type could not be controlled for, but this would be expected to weaken rather than exaggerate the observed association with SE status. As previously reported (Mayberry et al, 1995), there is a higher risk of MPA tumour subtype in younger patients. There was a previously unreported, excess risk of MPA subtype in patients with proximal subsites tumours and in women.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, the results show that least-deprived (affluent) patients are more likely to have tumours of MPA subtype and proximal subsite. It is possible that there has been a degree of under-ascertainment of MPA subtype in the study dataset À6.4% compared with about 13% reported in US studies (Mayberry et al, 1995;Chen et al, 1997), although it is unclear whether this difference represents under-diagnosis of MPA subtype in the UK or overdiagnosis in the US. For MPA-type underdiagnosis to bias the results, the quality of histopathological diagnosis would have had to differ by deprivation status, which is unlikely.…”
Section: Discussionmentioning
confidence: 85%
“…Analysis of the overall survival rate by ethnic group revealed that black patients (n=92) had a 5 year survival rate of 50%. This contradicts many earlier reports, in particular, studies in America where African American patients are reported to present late to clinicians, leading to an overall reduction in survival compared to white patients [12]. In the Network, 29.3% of the tumours in black patients were rectal cancer (C20) and 28.3% of the cancers (C18.0-18.3) were right sided; caecum to hepatic flexure.…”
Section: Discussioncontrasting
confidence: 66%
“…10,12 In our study, we observed significant differences in tumor stage, especially between blacks and whites. Because colorectal carcinogenesis progresses through a slow, multistage process, 2 the magnitude of racial differences for regional and distant tumors likely reflect delays in diagnosis, specifically, elapsed time from malignant transformation to cancer detection.…”
Section: Discussionmentioning
confidence: 45%
“…[5][6][7][8] Previous studies in the general population established that blacks with colorectal cancer were significantly more likely to be diagnosed at an advance stage and to have lower survival rates compared with whites. 6,9,10 In contrast, Asians/ Pacific Islanders and, in some reports, Hispanics have lower incidence and mortality from colorectal cancer than whites. 5,6 Although the exact mechanisms for racial disparities in colorectal cancer are not clear, the results of several studies suggest that inequalities in access to health care related to colorectal cancer prevention and treatment, including lack of health insurance or a regular source of care, may be important factors.…”
mentioning
confidence: 99%